The glass woman : a novel - Lea, Caroline (Harper, an imprint of HarperCollinsPublishers, 2019)
In the tradition of Jane Eyre and Rebecca,The Glass Woman by Caroline Lea, in which a young woman follows her new husband to his remote home on the Icelandic coast in the 1680s, where she faces dark secrets surrounding the death of his first wife amidst a foreboding landscape and the superstitions of the local villagers.